Convention, interest rates and monetary policy: a post-Keynesian–French-conventions-school approach - André de Melo Modenesi; Rui Lyrio Modenesi; José Luis Oreiro; Norberto Montani Martins (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This article aims at analysing the relationship between conventions and monetary policy using both the post-Keynesian and the French-conventions-school approaches, treated as complementary; and stressing the design of monetary policy frameworks (for example, inflation targeting) and the setting of interest rates as phenomena highly governed by conventions. The Brazilian monetary policy after the mid 1990s – marked by the highest real interest rates in the world – will be used as a case study.
Keywords: B20; E40; E43; E52; P16; 330; conventions; monetary policy; interest rates